CORRELATION BETWEEN LEIDENFROST TEMPERATURE, COOLING CAPACITY AND MACHINING TEMPERATURE: AN EXPERIMENTAL STUDY OF CUTTING FLUIDS - Gonçalves, D. M.; Sanchez, L. E. A.; Verdério Júnior, S. A. (Revista de Engenharia Térmica, 2021)
Much of the energy consumed by machining materials is converted into heat, which causes several technical and economic problems for the process. The cutting fluid application by the conventional method forms a vapor film of low thermal conductivity, which prevents direct contact between the fluid and the heated surface; the so-called Leidenfrost effect, which reduces cooling efficiency. Studies of this phenomenon applied to the machining of materials are still very restricted and scarce. In this sense, the present work experimentally studied the correlation of parameters Leidenfrost temperature, cooling capacity and machining temperatures, applied to the SAE 52100 steel turning process with conventional lubri-coolant, with different cutting fluids. The thermal properties of the studied cutting fluids were taken from the technical-scientific literature. An experimental apparatus was developed for measuring and acquiring machining temperatures. Synthetic cutting fluids were shown to have a better cooling capacity, followed by semi-synthetic fluids and emulsions. There is no relationship between Leidenfrost temperature, cooling capacity, and machining temperatures for the different types of cutting fluids studied.